SLAM DAS MINAS/AL: PERFORMANCE IN THE LITERARY SCENE: SLAM DAS MINAS/AL: PERFORMANCE IN THE LITERARY SCENE - Ferraz, Ana Flávia de Andrade; Simões dos Santos , Ticiane; Camelo de Macena Oliveira, Itailane; Mirela Marques Xavier, Willyane; de Lima Silva, Milenna (REVISTA ELETRÔNICA EXTENSÃO EM DEBATE, 2025)
The Slam das Minas/AL Project: performance in the literary scene, is a proposal to create a space for artistic experience by encouraging the writing and recitation of authorial poems with a protest and construction nature through marginal literature, which aims to enhance production and recognize the work carried out by female writers and poets inside and outside the university space, promoting the enjoyment of knowledge through the personal experiences of women, through spoken authorial poetry.